Psychological functioning of female teachers in menopausal periods - Poraj, Grażyna (Menopause Review/Przegląd Menopauzalny, 2009)
Objectives: The study makes an attempt to present psychological characteristics of female teachers in two important stages of their lives: the procreation period and menopause. The objective of the research was to find out if the period of menopause affects the teachers\' psychological qualities, such as feeling of safety, optimism, personality, and aggression syndrome, which are crucial as far as their job is concerned. Material and methods: Altogether 311 female teachers aged between 26 and 60 from the urban environment of the city of Łódź were examined. 59 women in the procreation period and 59 in the menopausal period were selected. The methods used in the research were: KPB Questionnaire to test the feeling of safety, NEO-FFI Inventory for measuring personality, LOT-R Questionnaire to estimate the level of optimism and IPSA to define the aggression syndrome. Results: The first stage of the research was devoted to comparison of the results of the teachers from the two selected groups. No significant differences were revealed between them taking into consideration the following qualities: safety, optimism, aggression syndrome as well as four features of personality. The only crucial difference concerned agreeableness. Menopausal teachers showed a higher indicator describing the above-mentioned trait. In further analysis of the results the researcher used cluster analysis, which allowed three groups of teachers to be distinguished, of different age and definitely different personal qualities, out of all 311 examined teachers. Each group was given a name corresponding to the results: “unstable” (93 women), “frustrated” (74 women) and “adapted” (144). The latter presented the most desired qualities. It is obvious that it is not the symptoms of menopause that denote psychological functioning of the examined women but the revealed individual differences. Conclusion: Individual psychological qualities of women are useful resources of resistance and it is these qualities that determine their functioning in various periods of their lives.